2018
DOI: 10.1002/jmv.25359
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in interferon λ3/interleukin‐28B gene and risk to noncirrhotic chronic hepatitis C genotype 3 virus infection and its effect on the response to combined daclatasvir and sofosbuvir therapy

Abstract: Hepatitis C virus (HCV) infection is a considerable public‐health problem and an important cause of liver disease with about 71 million people infected worldwide and more than 399 000 people die every year from hepatitis C‐related liver diseases. The present study was, therefore, initiated to investigate the association of polymorphism in interferon λ3 (IFNL3) also known as interleukin‐28B (IL‐28B) gene with chronic HCV infection and association of these polymorphic variants with the combination daclatasvir an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…The frequencies of rs12979860 and rs8099917 were 59.95% and 25.88% respectively. All four variations have been reported to impact drug effects in a large number of clinical trials involving antiviral regimens, including ritonavir, daclatasvir, sofosbuvir, ribavirin and interferon alpha 2b [ 38 40 ]. Therefore, rs8103142, rs12979860, rs8099917 and rs28416813 may also have a negative impact on the efficacy of these drugs in COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…The frequencies of rs12979860 and rs8099917 were 59.95% and 25.88% respectively. All four variations have been reported to impact drug effects in a large number of clinical trials involving antiviral regimens, including ritonavir, daclatasvir, sofosbuvir, ribavirin and interferon alpha 2b [ 38 40 ]. Therefore, rs8103142, rs12979860, rs8099917 and rs28416813 may also have a negative impact on the efficacy of these drugs in COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…They revealed that the CC genotype of IL-28B (rs12979860) was observed at a significantly higher frequency in patients with SVR (39.5%) compared to relapses (10.5%) and non-responders (17%), demonstrating the correlation of CC genotype with the probability of attaining SVR in contrast to non-CC variants. Moreover, the C allele was more prevalent in patients with SVR (65%), whereas the T allele was more prevalent in non-responders (62%) [14].…”
Section: Discussionmentioning
confidence: 98%
“…Previous findings of the treatment response demonstrated that the CC (main) genotype of IFN λ 3 (rs12979860) has been correlated with the possibility of attaining a better sustained virological response (SVR) to the combination of daclatasvir (DCV) and SOF treatment in genotype-3-infected HCV [14].…”
Section: Introductionmentioning
confidence: 99%